Genetic, phenotypic, and agronomic diversity of arrowroot (Maranta arundinacea) across agroclimatic zones for environmental adaptation and conservation - KACUNG HARIYONO; LULUK NOVIANA; MOHAMMAD UBAIDILLAH; AGUNG SIH KURNIANTO; ROSE NOVITA SARI HANDOKO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hariyono K, Noviana L, Ubaidillah M, Kurnianto AS, Handoko RNS. 2024. Genetic, phenotypic, and agronomic diversity of arrowroot (Maranta arundinacea) across agroclimatic zones for environmental adaptation and conservation. Biodiversitas 25: 3431-3441. Understanding the genetic and phenotypic diversity of crops like arrowroot is essential for developing sustainable agricultural practices and ensuring food security. This study, therefore, is of significant importance as it provides insights into how environmental factors influence trait variability, which can inform targeted conservation and agronomic strategies in the context of climate change. This study investigated the genetic, phenotypic, and agronomic diversity of arrowroot (Maranta arundinacea L.) across three agroclimatic zones in Jember District, East Java Province, Indonesia, with a focus on the impact of environmental factors on these traits. Sampling was conducted in Wuluhan, Sumbersari, and Arjasa subdistricts, covering 20 locations. Genetic analysis revealed that Arjasa presented the highest genetic diversity, with a median Genetics_Mean of 0.75 and an interquartile range (IQR) of 0.7-0.83, whereas Sumbersari and Wuluhan had median Genetics_Mean values of 0.8 and 0.8, respectively. Phenotypic diversity was also highest in Arjasa, with a Phenotypic_Mean of 0.83 (IQR: 0.78-0.86), whereas it was 0.8 in Sumbersari and 0.82 in Wuluhan. The quantitative traits presented less variability, with median Quantitative_Mean values of 0.22 in Arjasa, 0.19 in Sumbersari, and 0.21 in Wuluhan. The conservation priority index (CPI) was calculated, identifying Antirogo as the location with the highest CPI value of 0.440, indicating a high priority for conservation efforts. In contrast, Kebonsari had the lowest CPI value of 0.235. Principal component analysis (PCA) further highlighted the significant variability in genetic and phenotypic traits across sub-districts, particularly in Arjasa, where unique environmental conditions likely contribute to this diversity. The results emphasize the importance of targeted conservation strategies and agronomic practices to optimize the genetic and phenotypic potential of arrowroot, particularly in the face of environmental variability and global climate change.